Psycho-Emotional Burnout of the Personality in the Conditions of War - Prib, Hlib A.; Beheza, Ludmila E.; Markova, Marianna V.; Raievska, Yana M.; Lapinska, Tatyana V.; Markov Аrtur R. (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
A common cause of health disorders in war is psychotraumatic situations that lead to psycho-emotional burnout of military personnel. The purpose of the article is to conduct an empirical study of the psycho-emotional burnout of military personnel. Tasks are set: to determine the emotional reactions and states of military personnel; to assess the level of manifestation of emotional burnout of military personnel. Research Methods: The study used valid methods, "Diagnosis of the level of emotional burnout", "Determination of mental "burnout", and «Burnout Syndrome» in the professions of the «man-man» system, for the non-parametric data correlation variables, the Spearman coefficient. Results: The study revealed the military personnel’s inability to manage their emotions, which leads to depersonalization, personal alienation, and distance. The inadequate selective emotional response has 94.0%, which is an indisputable "sign of burnout". The peculiarities of emotion management of military personnel and their role in the genesis of emotional response in professional activity are revealed. It is established that the "economic manifestation of emotions" of military personnel can be manifested both in an excessively cheerful mood and aggression, which is frustrating behavior. Conclusion: In order to prevent psycho-emotional burnout, it is necessary to develop anti-stress skills, skills of controlling the manifestation of emotions based on critical analysis of the situation, and the ability not to throw out negative emotions on other people. To work with the military, it is necessary to substantiate the content of psychosocial counseling within the framework of a comprehensive system of psychological rehabilitation of servicemen.